MEDIA PEMBELAJARAN INTERAKTIF PADA APLIKASI PEAR DECK - Candra Kartika Putri (Jurnal Komposisi, 2021)
This study aims to determine the Pear Deck application as an interactive learning medium in Indonesian lessons regarding descriptive texts. The method used in this research is a qualitative descriptive method. The data in this study were obtained based on observations and written interviews conducted online. Junior high school level students (SMP) are the subjects in this study. Meanwhile, the object of this research is the use and use of the Pear Deck application as an interactive learning medium in Indonesian language learning related to descriptive text material. The source of this research data was obtained through the learning process carried out online or online with the research subjects using the Pear Deck application. Based on the results and discussion in this study, the Pear Deck application can be used for Indonesian language learning media because it can create interactive learning through the features provided.